Construction of a focal adhesion signaling pathway-related ceRNA network in pelvic organ prolapse by transcriptome analysis - Yu, Xia; He, Li; Chen, Ying; Lin, Wenyi; Liu, Hong; Yang, Xiu; Ye, Ying; Zheng, Xuemei; Yang, Zhenglin; Lin, Yonghong (Frontiers in Genetics, 2022)
Objective: Pelvic organ prolapse (POP) affects a large proportion of adult women. With the increase in global population ageing, which will impose a substantial medical burden. However, the pathogenesis of POP is still unclear. Herein, we aimed to explore the related RNAs regulating the occurrence of POP and provide potential biomarkers. Method: Tissue biopsies were taken from the anterior vaginal wall of six women with POP and six matched subjects without POP. The profiles of mRNAs, circRNAs, lncRNAs and miRNAs were obtained using whole transcriptome RNA sequencing. Result: The findings revealed that 195 circRNAs, 37008 lncRNAs, 135 miRNAs, and 2876 mRNAs were significantly altered (P < 0.05 and |log2FC| > 1). GO and KEGG enrichment analyses indicated that the differentially expressed genes (DEGs) were mainly enriched in the focal adhesion signaling pathway. FLT, ITGA9, VEGFD, PPP1R12B, and ROCK2 were identified as focal adhesion signaling pathway-related hub genes by protein–protein interaction network analysis. Based on the relationships between the DEGs and miRNA, lncRNA and circRNA targets, we constructed a focal adhesion signaling pathway-related ceRNA network. The ceRNA network includes hsa_circ_0002190 / hsa_circ_0046843 / lnc-CARMN -miR-23a-3p - ROCK2 and hsa_circ_0001326 / hsa_circ_0007733 / lnc-AC107959 / lnc-TPM1-AS - miR-205-5p - ROCK2 / PPP1R12B / VEGFD. Moreover, abnormalities in the cytoskeleton in fibroblasts from individuals with POP were observed. Conclusion: This RNA sequencing dataset can be used to discover new biomarkers and also may provide new insights into elucidating the pathological mechanisms of POP.